Disability and support relationships: What role does policy play?. Issue 1 (14th December 2018) - Fisher, Karen R.; Gendera, Sandra; Graham, Anne; Robinson, Sally; Johnson, Kelley; Neale, Kate
Abstract: Very little is known about how relationships between people with disabilities and their paid support workers are positioned in policy. With the policy shift toward choice of provider, individualised approaches, person centredness and self‐directed funding, the nature of their relationship assumes a more prominent role in the quality of support practice. The policy analysis in this article explores the extent to which current disability policy acknowledges, promotes, or diminishes the relationships between people with disabilities and workers, in their organisational context. It uses Honneth's conditions for recognition—love (cared for), rights (respected) and solidarity or social esteem (valued)—to understand how policy positions mutuality in the relationship. The policy review applied a three‐stage process: categorisation of policies, textual analysis and content analysis to policy documents at four levels—international, Australian federal, state and organisational in two case studies. The analysis revealed that while a rights framework is explicit in most policies, the emphases on the conditions for recognition within a relationship between people with disabilities and workers are compromised in instructional policies that attempt to manage the tension between choice and risk, particularly at the organisational level. Abstract : The analysis focuses on the extent to which disability policy acknowledges, promotes, or diminishes the relationships between people with disabilities and support workers. It reveals that while a rights framework is explicit in most policies, the conditions for recognition within the relationship are compromised in instructional policies that attempt to manage the tension between choice and risk.